DC Motor PID Control System for Tamarind Turmeric Herb Packaging on Rotary Cup Sealer Machine - Mila Fauziyah; Supriatna Adhisuwignjo; Lathifatun Nazhiroh Ifa; Bagus Fajar Afandi (Universitas Muhammadiyah Malang, 2022)
The end of this research is to find PID tuning value on the packaging automation process using the PID method. By finding the most suitable PID tuning value, a fast packaging process is obtained. Herbal ingredients in herbs that are left in the open for a long time tend to be damaged more quickly. So after the production process ends, the herbs must be packaged quickly. With the packaging automation method, the product can be hygienic and does not spoil quickly. One of the most widely and easy-to-use for automation methods in the industry is the PID control method because it can accelerate the system response, stabilize the system to match the setpoint and minimize overshoot. This study will discuss how the design of the PID control system using DC motor transfer function modeling in Matlab and the Second Ziegler-Nichols PID tuning method, the effect of the load on the motor response, and the effect of PID on the production speed. The system was tested with PID tuning values are Kp = 12, Ki = 12,506, Kd = 0.0028785, speed motor 24 RPM and a load of 3,160 Kg produces a good output response are delay time = 0.502 s, rise time = 0.804 s, settling time = 4.023 s, peak time = 133.084 s, Overshoot = 0.125% and Steady State Error = 0%. The effect of PID control on production speed is 83% faster than manual production and 29% faster than systems without PID.